Implementation of an Integrative Holistic Program in Early Childhood Education (Multi Site Study at the Pembina Inti State Kindergarten in Central Banjarmasin and Pembina East Banjarmasin State Kindergarten 2) - Nisa, Khairun; Novitawati, Novitawati; Sakerani, Sakerani (Formosa Journal of Applied Sciences, 2024)
This research aims to describe and analyze an integrative holistic program in early childhood education. This research uses a descriptive qualitative approach, multi-site design, with data collection through interviews, observation and documentation . The research results obtained regarding the implementation of an integrative holistic program in Early childhood education at Pembina Central Banjarmasin State Kindergarten and Pembina East Banjarmasin State Kindergarten 2 concluded that: 1) integrative holistic program planning in early childhood education is contained in the annual work program and standard operational procedures which are also contained in the operational curriculum of the educational unit. 2) Implementation of an integrative holistic program including education, health and nutrition, care, protection and welfare services involving collaboration with related parties across sectors.